Initial Treatment Patterns and Survival Outcomes of Mantle Cell Lymphoma Patients Managed at Chinese Academic Centers in the Rituximab Era: A Real-World Study - Wu, Meng; Li, Yun; Huang, Huiqiang; Xu, Wei; Wang, Yanyan; Huang, Haiwen; Zhao, Weili; Liu, Shuo; Xu, Pengpeng; Chen, Zhengming; Zhu, Jun; Song, Yuqin; et al. (Frontiers in Oncology, 2022)
Purpose: The aim of the study is to delineate disease characteristics, the initial treatment patterns, and survival in patients with mantle cell lymphoma (MCL) managed in the real world. Methods: Data of 518 MCL patients from 5 major Chinese Hematology Centers from the period of 2007 to 2017 were retrospectively analyzed. Results: The median age was 58 years. 88.6% of patients had ECOG PS 0-1, 80.7% had advanced-stage disease. Ki67 expression was <30% in 39.6% of patients, and 43.2% of patients were categorized in low-risk group based on MIPI scoring system. Overall, 73.4% of patients received rituximab in their first-line therapy. The most commonly used chemotherapy was CHOP-like regimen (45.2%), followed by high-dose cytarabine containing chemotherapy (31.3%) and bendamustine (3.3%). 13.7% (n=71) of patients underwent consolidative autologous stem cell transplant (ASCT), and 19.3% (n=100) received novel agents containing first-line regimens. With a median follow-up time of 52 months, the 3-year overall survival (OS) and 5-year OS were 73.7% and 61.4%, respectively. Age≤60, ECOG PS 0-1, stage I-II, normal LDH, absence of bone marrow involvement, Ki67 <30%, and lower risk IPI/MIPI scores were significantly associated with improved OS (p<0.05). The inclusion of rituximab improved 5-year OS with borderline significance (62.5% vs. 55.2%, p=0.076). High-dose cytarabine containing chemotherapy showed significant clinical benefit in 5-year OS (72.1% vs. 55.9%, p=0.010). Patients with ASCT had better 5-year OS in the younger (age≤60) group (87.2% vs 64.8%, p=0.002). Conclusion: This large retrospective data-set unequivocally confirmed the survival advantage afforded by cytarabine containing regimen and ASCT in a first-line setting under real-world management in the rituximab era.